Professionalization in the Third Phase of Teacher Training Aiming at Educational Standard Implementation: Theoretical, Methodological, and Empirical Challenges for Research in Geography Education for Geography Teacher Qualification - Applis, Stefan; Fögele, Janis (Journal of Geography Education, 2014)
The term "theory practice problem" denotes the challenges which emerge in the transfer of subject-didactic innovations to school practice. Reversely, the low integribility of theoretical reflections to the logics of practice is being criticised. This paper introduces and discusses two theoretical approaches using empirical examples from subject-didactic research projects on the professionalisation of geography teachers: the expert approach from cognitive psychology and the praxeological approach of the documentary method. Both are suitable for theoretical and empirical research on challenges in the implementation of competence orientation with teachers. In the framework of the discussion of theory and empirical analysis we examine if and how the convictions of teachers can be accessed. In doing so we focus on the components of professional knowledge and of convictions of teachers which are considered to be difficult to be modified as well as on their role for teaching and learning in the geography classroom. In this way we aim at building experience values led by theory which can contribute to the implementation of subject-didactic approaches in the framework of continuing teacher education.
Keywords: educational standards in geography, continuing teacher education, convictions of teachers, empirical classroom research, documentary method